Construction Law Reports - FURMSTON, Michael Philip (Institutional Knowledge at Singapore Management University, 2014)
This series of reports gives systematic coverage of the judgments of the Technology and Construction Court, the specialist court of the construction industry and appellate decisions therefrom. The series reports the full text of judgments, using approved transcripts.